Implementation of Coaching on Nursing Motivation and Workplace for Nurses to Reduce Burnout - Florentina Dhiana Sri Setyohariyati; Emiliana Tarigan; Havids Aima (Universitas Triatma Mulya, 2019)
Introduction. Burnout is a symptom that is often experienced by nurses, especially in the operating room, intensive unit and emergency room. Burnout is characterized by fatigue of heavy workloads, lack of control and appreciation, unfair treatment as employees, lack of social support at work, and conflict of value values that cause Emotional Exhausting, Depersonalization, Personal Accreditation. Coaching implementation by mentors to the implementing nurses is expected to reduce burnout. Methods. This study aims to analyze the description of the differences and influence of coaching implementation by mentor to the executor nurse burnout at Siloam Hospitals Group. Research uses quantitative methods with quasi experimental designs, pretest-posttest control group and causal research. The sample in the study was chosen by consecutve sampling in all respondents included in the inclusion criteria. The sample in this study amounted to 117 nurses, who were divided into 2 groups ie inetrvensi group with 88 respondents and control group with 29 respondents. Coaching implementation is given within 12 weeks with the frequency of meetings 3-4 times. Results. The results of this study showed that there was a decrease in burnout before and after intervention with paired t test in the intervention group and control group, with value (p = 0.002). Conclusion. The results of the intervention analysis on the implementation of coaching training simultaneously have an effect on motivation, workplace, age, gender, education and work experience simultaneously with a contribution of F 3,316 with a significance number of 0.005 <0.05. This study recommends the need for further research.